From Schumpeterian democracy to constitutional democracy - Pereira, Paulo Trigo (2022)
A critical issue of a constitutional democracy is to determine an optimal limitation of citizens’ political liberties. This problem is analysed here within the framework of a parliamentary system of government, and in the context of Rawls’ principle of equal political participation. It is argued that optimal barriers to entry into political competition are a function of the legislative decision rules, the domain of collective choices, and the rules for selecting (and dismissing) the executive. Contrary to Schumpeter and Riker who rejected ‘populism’ (the approach that public policy should be a result of citizens’ preferences), we argue that it is possible to reconcile greater citizen participation and liberal democracy with an appropriate institutional design.